2009
DOI: 10.1007/s00259-009-1110-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of stress myocardial ECG-gated perfusion imaging in asymptomatic patients with diabetic chronic kidney disease on initiation of haemodialysis

Abstract: Myocardial ischaemia, in addition to glycaemic control, is a strong prognostic marker for asymptomatic patients with diabetic CKD who are scheduled to start haemodialysis. Stress MPI is highly recommended for the management and therapeutic stratification of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
2
34
1
Order By: Relevance
“…Our previous studies and those of others have suggested that MPI can help predict outcomes among patients with suspected or extant CAD and those with CKD. [10][11][12][13] Although the incidence and severity of CVD are increased in patients with CKD, 1,3 routine screening has not yet been implemented in clinical practice. In addition, optional time-frame for screening for CVD among patients with CKD has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies and those of others have suggested that MPI can help predict outcomes among patients with suspected or extant CAD and those with CKD. [10][11][12][13] Although the incidence and severity of CVD are increased in patients with CKD, 1,3 routine screening has not yet been implemented in clinical practice. In addition, optional time-frame for screening for CVD among patients with CKD has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…19 The MPI defect score was relatively lower than those previously reported. [10][11][12][13] Since we excluded patients with CKD who had CAD, such a small defect might impact cardiac events in patients without such a diagnosis.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports indicated prognostic value of MPI suggested for patients with suspected or extant CAD and those with CKD. [8][9][10][11][12][13][14][15] The current report is a multicenter prospective cohort study in Japan to determine the ability of MPI to diagnose CAD and predict the outcomes of patients with CKD who are not definitively diagnosed with CAD (This study). The study aimed to clarify whether MPI can predict cardiac events and determine whether renal dysfunction combined with MPI abnormalities provides additional prognostic information to conventional markers.…”
mentioning
confidence: 99%
“…This finding seems to be concordant to the previous findings indicating importance of myocardial ischemia for CKD patient outcome. [10][11][12][13][14][15] In other words, CKD patients with severe myocardial ischemia with reduced eGFR with or without elevated CRP are suitable candidates for coronary angiography and subsequent coronary intervention in order to improve their outcome.…”
mentioning
confidence: 99%